Transnationalism, Intersectionality and Immigrant Lives: Critical Issues and Approaches to International Migration - Cheng, Zhiming; Tani, Massimiliano; Wang, Ben (Oxford University Press, 2022)
This chapter explores the relationship between the acquisition of English language skills and subsequent labour market outcomes of refugees and other groups in humanitarian need (e.g. asylum seekers) – which we jointly refer to as ‘humanitarian migrants’ in this chapter - using panel data from the Building a New Life in Australia (BNLA) survey. Since 2013 the Australian Government’s Department of Social Services has surveyed humanitarian migrants on a wide range of topics to understand the wellbeing and experiences in Australia of this group of settlers. The dataset surveys refugees and other humanitarian visa holders, and tracks individual humanitarian migrants on an annual basis. It is the largest longitudinal survey with this information in Australia. Our analysis pays particular attention to the role of language skills in recovering their pre-settlement human capital in the host country’s labour market, and the relevance of continuing public funding to provide formal language training programs to the humanitarian migrants who most need language skills.
Transnationalism, Intersectionality and Immigrant Lives: Critical Issues and Approaches to International Migration, 2023, Edward Shizha and Edward Makwarimba (editors), New York: Oxford University Press.
Language training and humanitarian migrants' host language skills: Recent Australian evidence
Keywords: Culture and language; Labour market; Migration and settlement